The interpreter as maternal container : (with specific reference to three Reagan-Gorbachev summits of the 1980s from the standpoint of the Soviet interpreters) /: (with specific reference to three Reagan-Gorbachev summits of the 1980s from the standpoint of the Soviet interpreters). (2022) - Blundy, Anna, 1970-
No abstract available